Case Report: PROS1 (c.76+2_76+3del) pathogenic mutation causes pulmonary embolism - Ding, Peng; Zhou, Yuan; Yang, Meijie; Li, Sheng; Zhang, Song; Zhi, Lijia (Frontiers in Cardiovascular Medicine, 2024)
Background Genetic variation plays an extremely important pathogenic role in the development of venous thromboembolism (VTE). Genetic protein S (PS) deficiency caused by PROS1 gene mutation is an important risk factor for hereditary thrombophilia. Case introduction In this case, we report a 28-year-old male patient who developed a severe pulmonary embolism during his visit. The patient had experienced one month of chest pains, coughing and hemoptysis symptoms. CTPA confirmed an acute pulmonary embolism with multiple filling defects in both pulmonary arteries. Ultrasound showed no thrombosis in the veins of both lower limbs. The patient's father and grandfather have a history of lower limb venous thrombosis. The patient was diagnosed with acute pulmonary embolism and pneumonia. The serum PS level significantly decreased (detection result: 10%, normal range: 77–143). Gene sequencing revealed a heterozygous missense mutation in PROS1 c.76+2_76+3del (base deletion), and further testing revealed that the genetic variation originated from his father. The patient was treated with heparin anticoagulant therapy, catheter thrombus aspiration, and catheter thrombolysis. After treatment, the patient's chest pain symptoms were relieved, and there were no symptoms such as difficulty breathing. On the 7th day of admission, the patient was transferred to a general hospital for further treatment. Conclusion Hereditary thrombophilia caused by mutations in the PROS1 (c.76+2_76+3del) gene is extremely rare. In clinical practice, heparin and rivaroxaban treatment are beneficial.